Studi Kelayakan Lingkungan Hutan Pendidikan Untuk Tujuan Ekowisata Alam KPH Unit XIII Halmahera Selatan - Sutari Sutari; Lily Ishak; Adnan Sofyan; Ramli Hadun; Andy Kurniawan; Aisjah Rachmawaty Ryadin (Universitas Khairun, 2025)
The Educational Forest in the Forest Management Area (KPH) Unit XIII, located in South Halmahera Regency, North Maluku Province, has the potential to be developed as a natural ecotourism area. One of the main functions of natural ecotourism is to preserve biodiversity and natural ecosystems in an area. However, available data on the potential of the educational forest environment for this purpose is still limited. Hence, this study was conducted with the aims of: 1) identifying the potential of an Educational Forest area; 2) analysing the level of suitability of the ecosystem within an Educational Forest; and 3) assessing the feasibility of an Educational Forest as a natural ecotourism destination. The findings of this study are expected to contribute to the development of the educational forest to be managed as a natural ecotourism destination. This research employs field observation and document analysis methods. Field observations were conducted within a sampling area of 2,500 m2 in each plot to collect data on the potency of the educational forest. This included assessing the types, thickness, and density of vegetation, as well as identifying the types of fauna present. Additionally, the components that contribute to the area's appeal, as well as the accessibility and accommodation options, were evaluated across five plots in the forest area. The potential data obtained were used to analyze the level of suitability and feasibility of this educational forest area as a natural ecotourism site. The document analysis included a review of various relevant literature to this research. The results of the study showed that the potential of the educational forest in the KPH Unit XIII includes the biotic potential comprising forest stand types such as Matoa trees, white Meranti (Shorea), banyan, Bugis wood, ironwood, galip nut, Calophyllum, and agarwood. In addition, the forest is home to a diverse range of fauna, including various species of birds, insects, reptiles, and several types of aquatic biota found in the rivers. Further, the educational forest area also possesses abiotic components including soil, water, sunlight, and a tropical climate. Another potential includes the beautiful natural scenery. Almost all types of vegetation were found in the five plots, with an even vegetation thickness of 50 m in each plot. The results of calculations on stand density showed that the highest density index value was found in plot V, namely 0.0076, with a total of 19 trees consisting of five types of trees. Plot III was in second place with a density index value of 0.0072 with a total of 18 trees consisting of five types of trees. Then followed by plot IV with a total density index value of 0.0064 with a total of 16 trees consisting of four types of trees. The lowest total density index value was found in Plot II at 0.0048 with a total of 12 trees consisting of four tree species. Meanwhile, the results of fauna potential observations found that almost all types of fauna are spread across all plots in the educational forest area. The suitability analysis results for the educational forest ecosystem indicated that the forest was classified as an S3 category or conditionally suitable for nature ecotourism, with an ecosystem suitability index value of 47.7%. The suitability level of this forest ecosystem was quite low due tolimiting factors, such as low stand density (0.1432 ind/m2). The low vegetation density was caused by high levels of illegal logging activity. To enhance vegetation density, a rehabilitation program is needed to replant the vegetation of the same types found in the forest area. The feasibility analysis results of the educational forest ecosystem as a natural ecotourism area showed that the Educational Forest Area had a feasibility level of 75.84% (S2). This suggests that the area is suitable for development as a natural ecotourism destination. This high level of suitability is supported by elements of attractiveness, accessibility, and adequate supporting infrastructures. One of the factors inhibiting the level of feasibility of the Educational Forest is the inadequate availability of accommodation. To support the development of the Educational Forest Environment as a natural ecotourism destination, it is necessary to develop decent accommodation facilities, such as rest areas, public toilets, security posts, hiking and camping facilities as well as information boards.